Trend and spatial clustering of medical education in Brazil: an ecological study of time series from 2010 to 2021 - Rafael Alves Guimarães; Ana Luísa Guedes de França e Silva; Marizélia Ribeiro de Souza; Adriana Moura Guimarães; Marcos Eduardo de Souza Lauro; Alessandra Vitorino Naghettini; Heliny Carneiro Cunha Neves; Fernanda Paula Arantes Manso; Cândido Vieira Borges Júnior; Alessandra Rodrigues Moreira de Castro; Victor Gonçalves Bento; Pablo Leonardo Mendes da Cruz Lima (BMC, 2023)
Abstract Context Studies that analyze the temporal trend and spatial clustering of medical education indicators are scarce, especially in developing countries such as Brazil. This analysis is essential to subsidize more equitable policies for the medical workforce in the states and regions of Brazil. Thus, this study aimed to analyze the temporal trend and identify spatial clusters of medical education indicators in Brazil disaggregated by public and private education, states, and regions. Methods A time-series ecological study was conducted using data from the Higher Education Census of the Ministry of Education from 2010 to 2021. The study analyzed vacancy density indicators of active and former students/100,000 population, disaggregated by public and private education, 27 states, and 5 regions in Brazil. Prais-Winsten regression was used for trend analyses of indicators. Hot Spot Analysis (Getis-Ord Gi*) was used to identify spatial clusters of indicators. Results The number of medical schools increased by 102.2% between 2010 and 2021. A total of 366 medical schools offered 54,870 vacancies at the end of 2021. Vacancy density and active and former students increased significantly in the period, but this increase was greater in private institutions. Most states and regions showed an increasing trend in the indicators, with higher increase percentages in private than in public schools. Hot spot spaces changed over time, concentrated in the southeast, center-west, and north at the end of 2021. Medical education remains uneven in Brazil, with a low provision in regions with low socioeconomic development, academic structure, and health services, represented by regions in the north and northeast. Conclusions There is a growing trend in medical education indicators in Brazil, especially in the private sector. Spatial clusters were found predominantly in the southeast, center-west, and north. These results indicate the need for more equitable medical education planning between the regions.